Implementasi Nilai-Nilai Moderasi Beragama Generasi Z dalam Bersikap di Ruang Digital - Surawijaya Ningsih, Bunga (Jisab, 2024)
This research discusses the role of generation Z in implementing the values of religious moderation in the digital space. The researcher intends to show a social picture of some information related to the behavior of generation Z in the digital space, especially in social media in implementing the values of religious moderation. Generation Z in Indonesia as the largest social media user in fact does not implement the values of religious moderation in their attitude and behavior on social media. This research is a descriptive qualitative research and uses the Library study research method. The results of the author's research explain the phenomenon that shows the low implementation of religious moderation values by generation Z on social media as evidenced by hoaxes, hate speech, and discrimination that are still carried out by Indonesian society. The values of religious moderation as the basis of people's lives should be practiced as guidelines in behaving and behaving in everyday life, including in social media. One of them is by practicing religious life by taking the middle way or how to avoid extreme actions or fanaticism. want division. The role of generation Z in supporting religious moderation is needed, among others, as social control in social media, being moderate or not too fanatical, being a good believer, spreading the importance of religious moderation and inviting in kindness.